Cyclin‐dependent kinase subunit2 (CKS2) promotes malignant phenotypes and epithelial‐mesenchymal transition‐like process in glioma by activating TGFβ/SMAD signaling - Fan Feng; Zongqing Zhao; Xuechang Cai; Xueyuan Heng; Ximeng Ma (Cancer Medicine, 2023)
Abstract Background Gliomas are a group of primary intracranial tumors with high morbidity and mortality. The previous researches indicated a crucial role of CKS2 (cyclin‐dependent kinases regulatory subunit 2) in hepatocellular carcinoma and breast cancer; however, little is known about the molecular mechanism of CKS2 in the tumorigenesis and epithelial‐mesenchymal transition‐like (EMT) process in glioma. Methods Datasets for bioinformatics analysis were obtained from the GEO, TCGA and CGGA databases. qRT‐PCR, western blotting (WB), and immunohistochemistry (IHC) assays were used to investigate the expression patterns of CKS2 among glioma and brain tissues. Glioma cells were transfected with small interfering RNA/overexpression plasmid against CKS2, then clone formation assay, CCK‐8, wound healing, Transwell assay, and flow cytometry were performed to detect changes in cell viability, invasiveness, and the apoptosis rate. Markers of cell invasion, apoptosis, EMT and TGFβ/SMAD signaling were evaluated by WB and immunofluorescence (IF) assays. Results We found that CKS2 overexpression correlates with poor prognosis in human glioma and knockdown of CKS2 could inhibit cell proliferation, migration, invasion, and induced apoptosis in glioma cells. Besides, we also found that knockdown of CKS2 could reverse the EMT process via modulating EMT‐related molecules. Glioma cells with overexpression of CKS2 were constructed to confirmed the fact that CKS2 induced nucleocytoplasmic translocation of SMAD2/3 and activated TGFβ/SMAD pathway, then upregulated its downstream targets expression, while inhibition of TGFβ/SMAD (by TGFβ inhibitor LY2157299 or SMAD4 siRNA) could reverse the tumor‐promoting effects and malignant phenotype caused by CKS2 overexpression. Conclusions We identified CKS2 as a critical contributor to the gliomagenesis, which might provide a novel therapeutic target for inhibiting the spread and infiltration of glioma.